Cardiovascular Risk in Systemic Autoimmune Diseases: Epigenetic Mechanisms of Immune Regulatory Functions - Chary López-Pedrera; Carlos Pérez-Sánchez; Manuel Ramos-Casals; Monica Santos-Gonzalez; Antonio Rodriguez-Ariza; Ma José Cuadrado (Clinical and Developmental Immunology)
Autoimmune diseases (AIDs) have been associated with accelerated atherosclerosis (AT) leading to increased cardio- and cerebrovascular disease risk. Traditional risk factors, as well as systemic inflammation mediators, including cytokines, chemokines, proteases, autoantibodies, adhesion receptors, and others, have been implicated in the development of these vascular pathologies. Yet, the characteristics of vasculopathies may significantly differ depending on the underlying disease. In recent years, many new genes and signalling pathways involved in autoimmunity with often overlapping patterns between different disease entities have been further detected. Epigenetics, the control of gene packaging and expression independent of alterations in the DNA sequence, is providing new directions linking genetics and environmental factors. Epigenetic regulatory mechanisms comprise DNA methylation, histone modifications, and microRNA activity, all of which act upon gene and protein expression levels. Recent findings have contributed to our understanding of how epigenetic modifications could influence AID development, not only showing differences between AID patients and healthy controls, but also showing how one disease differs from another and even how the expression of key proteins involved in the development of each disease is regulated.